Health, Nutrition, and Economic Development in Africa - Babatunde Omilola; N’doh A. Sanogo (Public Health, 2020)
The term “well-nourished populations” is the opposite of malnu-trition. According to the World Health Organization (WHO), mal-nutrition refers to deficiencies, excesses or imbalance in a person’s intake of energy and/or nutrients. The African continent faces the double burden of malnutrition (DBM) namely child undernutri-tion and adult/child obesity.1 Nutritional disparities and the DBM must be considered from a life course perspective.